Digital Marketing Strategies to Enhance Corporate Competitiveness in the Environmental Consulting Services Industry - Fikhar Athaurrahman Zada Sani; Kussudyarsana Kussudyarsana (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study examines digital marketing strategies employed by PT Seema Electra Sejahtera to enhance corporate competitiveness in the environmental consulting services industry. A qualitative approach with an intrinsic case study design was adopted to obtain an in-depth understanding of the company's digital marketing practices within its organizational context. Data were collected through semi-structured interviews with the President Director, Marketing Manager, and marketing staff, supported by non-participant observation, documentary analysis, and tertiary sources. Data credibility was ensured through source and methodological triangulation, member checking, and an audit trail, while analysis followed the interactive model of Miles and Huberman, including data reduction, data display, and conclusion drawing. The findings reveal that the company utilizes its corporate website, social media platforms, and search engine optimization (SEO) to improve visibility, disseminate service information, and strengthen its professional image. However, digital marketing has not yet become the company's primary marketing strategy because project acquisition remains largely dependent on LPSE, e-procurement systems, professional networks, corporate reputation, service quality, and repeat clients. Although supported by competent human resources and adequate technological infrastructure, the effectiveness of digital marketing is constrained by limited dedicated personnel, inconsistent digital marketing management, and the absence of systematic performance evaluation. The study recommends strengthening digital marketing integration to improve organizational competitiveness.